2018
DOI: 10.1002/jia2.25150
|View full text |Cite
|
Sign up to set email alerts
|

Using safe, affordable and accessible non‐steroidal anti‐inflammatory drugs to reduce the number of HIV target cells in the blood and at the female genital tract

Abstract: IntroductionAt its basic level, HIV infection requires a replication‐competent virus and a susceptible target cell. Elevated levels of vaginal inflammation has been associated with the increased risk of HIV infection as it brings highly activated HIV target cells (CCR5+CD4+ T cells; CCR5+CD4+CD161+ Th17 T cells) to the female genital tract (FGT) where they interact with HIV. Decreased HIV risk has been associated with a phenotype of decreased immune activation, called immune quiescence, described among Kenyan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…Despite condom usage and pre‐exposure prophylaxis (PrEP) as excellent prevention strategies, lack of accessibility in some developing countries and low adherence due to sociocultural factors continue to act as barriers in reducing the HIV epidemic. Alternative interventions have been studied to be used as additional prevention strategies, such as male circumcision, post‐exposure prophylaxis (PEP), PrEP, and, more recently, the induction of T cell immune quiescence (IQ) at the FGT . Table presents examples of vaginal microbicide clinical trials designed for the prevention of HIV infection.…”
Section: Current Human Immunodeficiency Virus Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…Despite condom usage and pre‐exposure prophylaxis (PrEP) as excellent prevention strategies, lack of accessibility in some developing countries and low adherence due to sociocultural factors continue to act as barriers in reducing the HIV epidemic. Alternative interventions have been studied to be used as additional prevention strategies, such as male circumcision, post‐exposure prophylaxis (PEP), PrEP, and, more recently, the induction of T cell immune quiescence (IQ) at the FGT . Table presents examples of vaginal microbicide clinical trials designed for the prevention of HIV infection.…”
Section: Current Human Immunodeficiency Virus Epidemiologymentioning
confidence: 99%
“…A recently published study by Lajoie et al ., presents a clinical trial on low‐risk HIV seronegative women from Nairobi (Kenya) taking either HCQ or acetylsalicylic acid orally for 6 weeks. This study showed that low‐dose oral HCQ reduced systemic immune activation and oral acetylsalicylic acid is capable of reducing systemic and mucosal activated immune cells …”
Section: Current Human Immunodeficiency Virus Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations